(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Liver cancer (LC) represents a significant global health burden, characterized by poor prognosis and requiring substantial efforts for effective control and improved outcomes. This study aimed to evaluate changes in peripheral blood white blood cell counts (WBC) among patients with chronic liver diseases (CLD) having hepatitis B virus (HBV) infection. Methods: A cross-sectional descriptive study was conducted, analyzing data from 100 patients with HBV-related primary hepatocellular carcinoma (HCC), 25 patients with HBV-related cirrhosis (HBC), 25 patients with chronic hepatitis B (CHB), and 50 healthy controls (HC). Results: WBC counts decreased progressively from the HC group to the CHB and HBC groups. Notably, WBC counts were significantly lower in HBC patients, compared to healthy controls (p < 0.05). In contrast, WBC counts were elevated in HCC patients relative to both the HBC group and the combined (HBC + CHB) group (p < 0.01). WBC count demonstrated the ability to distinguish HCC from HBC and the (HBC + CHB) group, with respective AUC values of 0.6934 (p = 0.0028) and 0.65 (p = 0.0028). At the optimal cutoff value (WBC > 4.945), WBC count showed high sensitivity in diagnosing HCC among chronically HBV-infected individuals, with a sensitivity of 87.9% and a low specificity of 41.20%. Conclusion: WBC counts were reduced in HBC patients but increased in HCC patients, suggesting that elevated WBC may serve as a potential indicator of malignant transformation. WBC count showed discriminatory power in identifying HCC among patients with other CLD, such as CHB and the combined CHB + HBC group, with high sensitivity. As a readily accessible, non-invasive, and cost-free parameter, WBC may be a useful tool for HCC screening in patients with HBV-related cirrhosis.